About the Control of the Underwater and Above Water Nuclear Explosions by Hydroacoustic Methods - Adushkin, V. V.; Khristoforov, B. D. (1995)
The analysis of the experimental data available at the IDG which may be applicable to the problem of the detection and identification of nuclear explosions by modern hydroacoustic methods is represented. These data includes some results of observations of nuclear explosions at the Novaya Zemlya test site; results of measurements of HE with weights to 100 kg at a shallow reservoir; explosions of deep water bombs and mines; modeling of explosions of small charges of HE including underwater explosions in cavities filled by air. On the basis of the analysis of the experimental data it was shown that methods of hydroacoustic control can be used for the detection and identification of nuclear explosions, which were conducted near bottom or the free surface of water, above water and at reservoir's coast including underground explosions. Application of high sensitive hydrophones established near the bottom of sea with low level of noise, existence of sound channels with small attenuation favor this inspection. From nuclear explosions conducted in confined reservoirs similar to the Bay of Chernaya, hydrophones can received signals in open sea from seismic waves before shock waves in water. These tests shows strong reducing effect of the bottom and free surface of the reservoir on the acoustic efficiency. Thus, it is necessary to conduct a special investigation for determining the advantages and disadvantages of the methods of hydroacoustic control respective to different methods. Special acoustic source function was developed which allows to determine parameters of acoustic signal at large distances before the acoustic wave comes into sound channel. Acoustic signals from various sources of natural and artificial origin: HE, impact of meteorites, earthquakes, tsunami and so on are used for identification of nuclear explosions. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p960-967.